Valvular Heart Disease and Pregnancy in the Delivery Room at Yalgado Ouedraogo University Hospital about 12 Cases - Koudougou, Jonas Kologo; Georges, Rosario Christian Millogo; Mbaye, Salissou Seck Mbaye; Relwendé, Aristide Yaméogo; Hermann, Adoko; Germain, Mandi; W, Bernard Ouedraogo; Adolphe, Zingué; Anna, Thiam/Tall; André, K. Samadoulougou (Journal of Hypertension and Cardiology, 2022)
This series summarizes 12 pregnancies complicated by valvular heart disease, focusing on intrapartum management, anesthesia choices, and maternal–fetal outcomes in a resource‑limited setting.
Keywords: Heart; congenital; pregnancy